The new variant of the Creutzfeldt-Jakob disease accounts for no relative increase of the Creutzfeldt-Jakob disease mortality rate in the United Kingdom; this fits ill with the new variant being the consequence of consumption of food infected with the agent of Bovine Spongiform Encephalopathy - Hénaut Alain; Laprevotte Ivan (BMC, 2003)
Abstract Background A new variant of Creutzfeldt-Jakob disease was described in the United Kingdom. It is often claimed that it is caused by consumption of food infected with the agent of bovine spongiform encephalopathy. However, this remains open to question because the number of cases of the variant is, at the present time, less than would be expected from a major food-borne source. Discussion The EUROCJD cooperative study presents currently available epidemiological data of Creutzfeldt-Jakob disease and its new variant, for nine European countries plus Australia and Canada. Unexpectedly, for the United Kingdom where all but a few cases of the new variant have been reported, these cases have to be included in the incidence curve of the sporadic forms of the disease in order to obtain the best fit with the median curve from all the countries. This variant could be merely a rare clinical phenotype within the sporadic disease. The published clinical and experimental data which suggest that it is linked with bovine spongiform encephalopathy, lead us to propose that this link could be a common etiological origin other than consumption of bovine infected food. In any case, public health recommendations hold and further investigation is required. Summary The lack of a relative increase of the Creutzfeldt-Jakob-disease mortality rate in the United Kingdom, does not fit well with the new variant being the consequence of consumption of food infected with the agent of bovine spongiform encephalopthy.